PENGARUH SET KESEMPATAN INVESTASI DAN KEPEMILIKAN MANAJEMEN TERHADAP PEMBAYARAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tri Rahmawati, Christina Heti (Widya Warta, 2017)
The purpose of the research was to examine: (1) the effect of investment opportunity set on dividend payout at the firms listed at Indonesia Stock Exchange at period 2013-2015 and (2) the effect ofÂ  investment opportunity set on dividend payout with insider ownership as a moderating variable at the firms listed at Indonesia Stock Exchange at 2013-2015 period. The population in this research was all of the firms listed at Indonesia Stock Exchange at 2013-2015 period, namely 266 firms. The samples were taken with purposive sampling method; they were 35 firms. The criteria of the firms becoming samples were (1) having insider ownership and (2) having amount of stocks to be sold. The data collection technique was using documentation of the center of stock exchange data, Faculty of Economics and Business UGM. The data analysis method was multiple linear regression. The analysis showed that the investment opportunity set had a negative impact on dividend payout, while the insider ownership strengthened the relationship.